Modelo de gestión administrativa para el fortalecimiento de la competitividad de la empresa textil Lolystore - Jácome, Sammy T. (2019)
The present study called administrative management model for the improvement of the competitiveness of the textile company Lolystore, which had as its general objective To propose a model of administrative management for the improvement of the competitiveness of the company Lolystore located in the canton Otavalo during the year 2019. It allowed research on administration, management, logistics, competitiveness among others. on the other hand, the implemented methodology was of a quantitative nature, being a field investigation, with projective methodology, as a technique to obtain data, a survey was applied that was applied to the operators of the company and three interviews which were applied to the owner Mrs. Dolores Maigua who serves as administrative manager and logistics operations, and the sales staff of the company, they threw the need to implement an administrative management model that would improve the competitiveness of the company in the market textile, in the same way the evaluation of the internal and external factors was carried out by means of the realization of a foda analysis, which determined the factors of great relevance for the realization of the management model, likewise it was proceeded to create the mission, vision, values, policies, objectives, functional organizational structure as well as the competitiveness strategy that allows the improvement of the same in the company. On the other hand, the impact that the project generated in different areas, such as commercial, administrative, technological, educational and social, was measured, in order to then determine the overall impact of the project, showing a positive means that the feasibility of the project within The company finally the owner and employees of the company declared as very appropriate the administrative management model, wishing to implement it as soon as possible in order to obtain the goals and achieve competitiveness within the textile market.